Efecto del potasio en la producción y calidad del fruto en el cultivo del café en la región litoral del Ecuador - Calero López, Alex Alfredo (2021)
Las In Ecuador, coffee is one of the traditional crops of all time, our country being one of the few to produce two types of coffee, Arábica (Coffea arabica) and Robusta (Coffea canephora). Arabica coffee production is concentrated in the provinces of Manabí, Loja, and the western cordillera area, while robusta coffee is mostly grown in the Ecuadorian Amazon. The importance of potassium fertilization is vital in coffee production, favoring vegetative growth, enzymatic stimulation and inducing plant resistance against the attack of pests and adverse conditions. Correct potassium fertilization during the reproductive stage of coffee cultivation favors flowering, fruit retention and production per plant. Potassium contributes directly to the quality of coffee as a drink, by stimulating the enzymatic activity of polyphenoloxidase, which favors the quality of aroma and flavor of the drink. The main potassium fertilizers used in the nutrition of coffee crops are potassium chloride (KCl), potassium sulfate (K2SO4) and potassium nitrate (KNO3), with 60%, 50% and 44% of K20 respectively, being this like this item. The doses of potash fertilizers vary according to various factors, with averages from 200 kg/ha/year to 260 kg/ha/year in cropping systems with a density of 5000 to 7500 plants per ha respectively.